Empathic Listening as a Transferable Skill - Gritten, Anthony (Empirical Musicology Review, 2015)
<span style="font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: Mangal; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">This text responds to Deniz Peters’ argument with three things: a broad context for empathic listening based on its value as a transferable skill; a comment on the relationship between musical empathy and “social empathy via music”; and a comment on the “indeterminacy” at the beginning of empathic listening.